The future of higher education (HE) hangs on innovating our assessment – but are we ready, willing and able?. Issue 1 (1st January 2020) - Knight, G. L.; Drysdale, T. D.
ABSTRACT: Graduates are entering a sociotechnological world, with teaching and assessment needing to reflect that, by shifting from a 'recall-on-paper' to 'do-it-for-real'. With increasing student numbers, it is not feasible to have staff-student ratios and round-the-clock availability required to provide instant feedback and ever-more interactive teaching sessions, so digital solutions are the only option. There is already growing comfort with using computers in formal assessment; however, more work is required to extend beyond performance indicators enabling digital assessments, to addressing how students apply their learning to relevant work-based scenarios. This opinion piece discusses the issues HE currently face to ensure students develop the employability skills that equip them to be proficient in the skills directly related to their degree subject but also transferable to other graduate careers. It raises possible solutions to current technological problems in developing more computer-based assessment, to enable academics to design assessments that develop the capabilities students need.